Pengaruh Tingkat Salinitas yang Berbeda terhadap Kelangsungan Hidup Benur Udang Windu (Penaeus Monodon) Pl 10 Selama Transportasi Sistem Basah Tertutup - Erdendy Firmansyah; Achmad Kusyairi; Sri Oetami Madyowati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2026)
The transportation of tiger shrimp postlarvae (Penaeus monodon) in aquaculture practice is a critical stage as it may induce physiological stress that directly reduces survival rate. Salinity, as a water quality parameter closely associated with osmoregulatory processes, is a key determinant of success in closed wet system transportation. The present study was designed to examine how varying salinity concentrations influence the survival percentage of PL 10 tiger shrimp postlarvae subjected to closed wet transport conditions, as well as to identify the most suitable salinity range for such transport. A Completely Randomized Design (CRD) was employed with five salinity levels as treatments — 10, 15, 20, 25, and 30 ppt — each replicated five times. Each experimental unit contained 1,500 postlarvae in 1 L of oxygenated water packed in plastic bags and transported for approximately 3 hours. The main parameter observed was survival rate (SR), while supporting parameters included temperature, dissolved oxygen (DO), and pH. Statistical evaluation included the Kolmogorov–Smirnov normality test, Levene’s test for variance homogeneity, one-way analysis of variance (ANOVA), and Duncan’s Multiple Range Test (DMRT) at a significance level of α = 0.05. Results showed that salinity differences had a highly significant effect on postlarvae survival rate (Sig. = 0.000 < 0.05). The 25 ppt salinity treatment produced the highest survival rate of 99.64%, while 10 ppt resulted in the lowest at 63.78%. The measured water quality variables — temperature, dissolved oxygen, and pH — did not exert a statistically significant effect on postlarvae survival throughout the transport period.